Intelligent Food Packaging model for Industry 4.0 (International Journal of Food and Nutritional Sciences, 2022)
In the era of Industry 4.0, characterized by interconnectedness and automation, the foodpackaging industry stands poised for transformative change. This study presents an innovativeIntelligent Food Packaging (IFP) model tailored for Industry 4.0 environments.